Analisis Perbandingan Biaya Struktur Pembangunan Rumah Metode RISHA dan Konvensional di Kabupaten Minahasa Selatan, Sulawesi Utara - Ahmad Waris,; Okta Meilawaty,; Veronika Happy Puspasari, (Journal Serambi Engineering, 2023)
RISHA innovation is a variation of precast cement created by the Center for Settlement Research and Development, Ministry of Public Works and Public Housing. The aim of this research is to determine the comparison of the use of structures using the RISHA and conventional methods in South Minahasa Regency. This research is a type of descriptive and comparative research. Primary data in this research was collected by direct observation and interviews, while secondary data was collected by means of literature study. This research was conducted in March-June 2023 located in South Minahasa Regency, North Sulawesi Province. The results of the research between the RISHA and conventional methods showed that the cost difference in building structures including sloofs, columns and beams was Rp. 2.589.926,52 atau 5,30 % greater for the conventional method and for wall work using the RISHA method using lightweight bricks amounting to Rp. 18,030,415.00 while the conventional method with red brick walls is Rp. 16,585,245.00 with a difference of Rp. 1,444,751.00 or 8,01 %. However, the RISHA method can affect plastering and wall plastering work where the RISHA method has a smaller wall area because the sloof, column and ring balk sections of the RISHA method no longer need to be plastered and plastered so it is more efficient/cheaper than the conventional method.